2020
DOI: 10.1109/access.2020.2983053
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Centrality of Influential Nodes Identification in Complex Networks

Abstract: Influential nodes identification in complex networks is vital for understanding and controlling the propagation process in complex networks. Some existing centrality measures ignore the impacts of neighbor node. It is well-known that degree is a famous centrality measure for influential nodes identification, and the contributions of neighbors also should be taken into consideration. Furthermore, topological connections among neighbors will affect nodes' spreading ability, that is, the denser the connections am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Yang et al [2], presented a novel mixed centrality measure which is consider as degree and clustering coefficient (DCC).DCC is defines based on four parts: effect of degree, neighbor's degree, clustering coefficient, and next level neighbor's clustering coefficient. The advantage of this mixed centrality measure is less time complexity which is O (nk 2 ) where n is number of node in the network and k is average degree.…”
Section: Mixed Centrality Measuresmentioning
confidence: 99%
“…Yang et al [2], presented a novel mixed centrality measure which is consider as degree and clustering coefficient (DCC).DCC is defines based on four parts: effect of degree, neighbor's degree, clustering coefficient, and next level neighbor's clustering coefficient. The advantage of this mixed centrality measure is less time complexity which is O (nk 2 ) where n is number of node in the network and k is average degree.…”
Section: Mixed Centrality Measuresmentioning
confidence: 99%
“…Chen et al [33] claim that influential nodes can be identified by extracting and synthesizing topology feature information of traditional centrality indices and spreading influence. Yang et al [34] identify the influential nodes by incorporating the degree and clustering-coefficient of neighbor nodes. Berahmand et al [35] incorporate the natural characteristics of complex networks to capture the spreader node.…”
Section: B Network Centralitymentioning
confidence: 99%
“…The spread of a virus outbreak (such as Covid-19) can be estimated and precautions can be taken based on this [8]. By modeling the spread of gossip on the social network, the spread can be prevented [9], [10]. Or, the desired information may reach the maximum number of people [11].…”
Section: Introductionmentioning
confidence: 99%